Raised chondroitin sulphate WF6 epitope levels in gingival crevicular fluid in chronic periodontitis - Sakornrat Khongkhunthian (2018)
Aim: To determine the levels of chondroitin sulphate (CS) WF6 epitope, recognized by WF6 monoclonal antibody, in gingival crevicular fluid (GCF) from different stages of periodontal disease and healthy periodontium, and to correlate those levels with clinical parameters. Material and Methods: GCF samples, collected from 389 sites, were analysed for the WF6 epitope levels by the competitive enzyme-linked immunosorbent assay. Results: The median WF6 epitope level was significantly higher in chronic periodontitis sites (n=185) than in healthy and gingivitis sites (n=204) (p<0.001), whereas the median levels did not significantly differ between healthy (n=65) and gingivitis sites (n=139). The median level in severe periodontitis sites (n=60) was significantly higher than that in moderate periodontitis sites (n=63) (p=0.019). Similarly, the median level in moderate periodontitis sites was significantly higher than that in slight periodontitis sites (n=62) (p=0.001). The WF6 epitope levels significantly correlated with probing depth (r=0.777, p=0.001) and loss of clinical attachment level (r=0.814, p=0.001). Conclusion: Elevated CS WF6 epitope levels in GCF are associated with severity of periodontitis. The WF6 antibody may therefore be clinically applied to monitor disease severity and progression. © 2008 Blackwell Munksgaard.